PENINGKATAN TATA KELOLA KEPARIWISATAAN BAHARI MENGGUNAKAN SIGNING BLUE ASSESSMENT DI PRATASABA RESORT KABUPATEN BERAU KALIMANTAN TIMUR: PENINGKATAN TATA KELOLA KEPARIWISATAAN BAHARI MENGGUNAKAN SIGNING BLUE ASSESSMENT DI PRATASABA RESORT KABUPATEN BERAU KALIMANTAN TIMUR - Sufriady Syam (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
Tourism is developing expeditiously, with particular interest in maritime activities. previously mentioned, it can obtain negative ramification, such as heightened household waste, environmental pollution, ecological damage, commination to species and conflicts over ownership. Pratasaba Resort's designation blue rating aims to enhance responsible tourism governance and motivate communities to participate in Indonesia's marine conservation efforts. The methods used are interviews, observations, document reviews, media research, and determining the position of economic participants in the Signing Blue rating. Based on the assessment results, Pratasaba Resort needs to improve all the rage several areas, including: B. (1) Starfish 1: Understanding and commitment to consistent tourism practices. (2) Starfish 2: Commitment to implementing collaborative governance practices. (3) Starfish 3: Increased stakeholder awareness, motivation and commitment in tourism practices. Overall, Pratasaba Resort Maratua was able to achieve Starfish 3 level. This means that it was fully committed to consistent tourism activities and can carry them out domestic.